Optimizing silica extraction form rice ash: a comparative study of alkaline and acid leaching / Mohammad Yushaiman Habib Md Yusof and Mimi Azlina Abu Bakar - Md Yusof, Mohammad Yushaiman Habib; Abu Bakar, Mimi Azlina (Penerbit UiTM (UiTM Press), 2025)
This research aimed to study the characteristics of silica which had been extracted from rice ash using two methods, i.e.alkaline and acid leaching. There were five types of solutions used; 1M and 2M sodium hydroxide (NaOH) solutions, 1M and 2M potassium hydroxide (KOH) solutions, and a 1M hydrochloric acid (HCl) solution. After the extraction process, the amount of silica was calculated and analyzed using FTIR and XRD.